Profitabilitas, Ukuran Perusahaan, Pengungkapan Corporate Social Responsibility dan Nilai Perusahaan - Hermawaty, Nadia; Sudana, I Putu (E-Jurnal Akuntansi; Vol 33 No 5 (2023), 2023)
Firm value is an important indicator for investors as a consideration for investment decisions. The research aims to obtain empirical evidence of the effect of profitability, firm size and disclosure of corporate social responsibility on firm value. This research was conducted on various industrial sector companies listed on the Indonesia Stock Exchange. The sample was determined using a purposive sampling method of 69 observations. The collected data were analyzed by multiple linear regression. The results of the study explained that profitability has a positive effect on firm value, firm size has a negative effect on firm value and disclosure of corporate social responsibility has no effect on firm value. The research results are able to support signal theory and agency theory and can provide information to investors in making investment decisions by linking them to firm value. Keywords: Profitability; Firm Size; Corporate Social Responsibility Disclosure; Firm Value.